Crosslinking of peanut allergen Ara h 2 by polyphenol oxidase: digestibility and potential allergenicity assessment. (19th January 2016) - Wu, Zhihua; Lian, Jun; Han, Yuanlong; Zhou, Ningling; Li, Xin; Yang, Anshu; Tong, Ping; Chen, Hongbing
Abstract: BACKGROUND: Peanut is one of the eight major food allergens. Its allergen, Ara h 2, can be recognized by over 90% of serum IgE samples from peanut‐allergic patients. Therefore, reducing the allergenicity of Ara h 2 is especially important. RESULTS: In the present study, polyphenol oxidase (PPO), a protein cross‐linking reaction catalyst that acts on tyrosine residue, was used to modify Ara h 2. After crosslinking, the microstructure, digestibility, IgG binding capability and IgE binding capability of Ara h 2 were analyzed. Cross‐linking decreased the potential allergenicity of Ara h 2 by masking the allergen epitope, while the antigenicity of Ara h 2 changed slightly. After crosslinking, the apparent diameter of Ara h 2 was altered from 300 to 1700 nm or 220 nm, indicating that polymerization could either be inter‐ or intramolecular. Regarding digestibility, crosslinked Ara h 2 was relatively more easily digested by gastric fluid compared with the untreated Ara h 2, but much more difficult in the intestinal fluid. CONCLUSION: The crosslinking reaction catalyzed by PPO, as a non‐thermal process, may be beneficial for avoiding food allergy. The reaction could mask allergen epitopes, decreasing the allergenicity of Ara h 2. © 2015 Society of Chemical Industry